Penggunaan Model Problem Based Instruction Terhadap Peningkatan Prestasi Belajar Siswa Kelas IV SDN XXV Wailiti - Lukas Bera (Peneliti.net, 2021)
The purpose of this study was to determine the positive and significant effect on the application of the Problem Based Instruction model on learning achievement. This research is a type of quantitative research, aiming to see the effect of student achievement on social studies subjects with material on ethnic diversity through the Problem Based Instruction model for fourth grade students at SDN XXV Wailiti. The subjects in this study were fourth grade students in the 2018/2019 academic year with 30 students in the experimental class. This research is motivated by the low learning achievement in social studies learning. One of the solutions taken to overcome these problems is learning by using the Problem Based Instruction model so that learning is more interesting and more meaningful. The results of observing student activities in the experimental class using the Preoblem Based Instruction model are seen in the results of observing the activity of students in the learning experiment class reaching an average value of 82.66, the results of the observations being in a good category. It was found that the learning outcomes in the experimental class using the Problem Based Instruction model, the average value in the experimental class pretest learning outcomes was 49.9 with classical completeness of 49.9% while the average posttest learning outcomes in the experimental class was 64.8 with completeness classical by 64.8%. Student learning outcomes have changed for the better after using the Problem Based Instruction model with ethnic diversity material. Based on the research achievement indicators, it can be concluded that the use of the Problem Based Instruction model has a positive effect on student learning achievement at SDN XXV Wailiti, Wolomarang Village, Alok Barat District, Sikka Regency for the 2019/2020 academic year.